Contribution of Forensic Laboratory Examination Results in Proving Narcotics Crimes - itok (edujavare, 2024)
The results of forensic laboratory examinations are included in documentary evidence that can prove that a crime has occurred. In practice, there is a narcotics crime that requires a forensic laboratory examination related to the alleged narcotics crime. This research aims to analyze the role of forensic laboratory examination results as documentary evidence. These problems are analyzed using normative legal research methods with a case approach. The results of this research show that the results of forensic laboratory examinations of substances suspected of being narcotics play a very important role in proving that a crime of illicit narcotics trafficking has occurred.